Penguatan Pendidikan Karakter Nilai Religius Dalam Program Kegiatan Budaya Sekolah - Annek Astri Octaviani; Furaidah Furaidah; Sri Untari (Graduate School of Universitas Negeri Malang, 2019)
Abstract: This research aims to describe the program's cultural activities as a deciding of the quality of the school. This research uses qualitative research methods with descriptive type. The results of this research, namely, programs for strengthening the character education religious values that exist in the school consist of extracurricular, co-curricular and cultural school. But the quality of a school is determined from the culture of the schools it has set. This is because the program of extracurricular and co-curricular activities is not every day executed by learners. So that the character resulting from the program of extracurricular and co-curricular activities is not as much as the program of school culture activities that are applied everyday. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan program-program kegiatan budaya sekolah sebagai penentu dari mutu sekolah. Penelitian ini menggunakan metode penelitian kualitatif dengan jenis deskriptif. Hasil penelitian ini, yaitu program-program kegiatan penguatan pendidikan karakter nilai religius yang ada di sekolah terdiri dari krgiatan ekstrakurikuler, co-kurikuler, dan budaya sekolah. Akan tetapi, mutu dari sebuah sekolahan tersebut ditentukan dari budaya sekolah yang diterapkannya. Hal tersebut dikarenakan pada program kegiatan ekstrakurikuler dan co-kurikuler tidak setiap hari dijalankan oleh peserta didik. Jadi, karakter yang dihasilkan dari program kegiatan ekstrakurikuler dan co-kurikuler tidak semaksimal program kegiatan budaya sekolah yang diterapkan setiap hari.